Exploring stigma and social norms in women's abortion experiences and their expectations of care. Issue 3 (29th November 2019) - Makleff, Shelly; Wilkins, Rebecca; Wachsmann, Hadassah; Gupta, Deepesh; Wachira, Muthoni; Bunde, Wilson; Radhakrishnan, Usha; Cislaghi, Beniamino; Baum, Sarah E
Abstract: Abortion is a common and essential component of sexual and reproductive health care, yet social norms and stigma influence women's decision-making and create barriers to safe abortion care. This qualitative study in Kenya and India explores abortion-related fears, expectations and perceptions of stigma among women who have obtained abortion services. In 2017, we conducted 34 semi-structured interviews and 2 focus groups with women who had obtained abortion services in Maharashtra state in India and Thika and Eldoret in Kenya. Thematic analysis was informed by the individual-level abortion stigma framework and theory of normative conduct. We aimed to learn about the diversity of women's experiences, analysing pooled data from the two countries. Most participants reported that before seeking abortion they had little prior knowledge about the service, expected to be judged during care, and feared the service would be ineffective or have negative health consequences. Many reported that community members disapprove of abortion and that a woman's age or marital status could exacerbate judgement. Some reported limiting disclosure of their abortion to avoid judgement. Negative stories, the secrecy around abortion, perceived stigma, social norms, and fear of sanctions all contributed to women's fears and low expectations. These findings elucidate the relationship between social norms and stigma and how expectations and concerns affect women's experiences seeking care. The results have implications for practice, with potential to inform improvements to services and help organisations address stigma as a barrier to care. This may be particularly relevant for younger or unmarried women.